The Initial Performance of Commonly Used Primary Support on U.S. Coal Mines - Murali Gadde (International Conference on Ground Control in Mining, 2011)
U.S. coal mines? primary roof supports typically consist of passive resin bolts; however, the use of active bolt systems is increasing. Despite this widespread use, a comparative performance evaluation of these bolt systems has not been done under similar geologic conditions. The performances of three commonly used primary bolt systems were investigated: fully grouted passive rebar, fully grouted tension rebar (using two speed setting resin), and resin-assisted rebar with mechanical anchors. In order to investigate the performance of these bolts, strain gauged bolts of all three types were installed at three different coal mines as part of a larger research project funded by the National Institute for Occupational Safety and Health (NIOSH). This paper addresses the initial installation bolt loads measured at these mines. Analysis of the data showed much lower installed loads on active bolts than is traditionally assumed. It appears that the active load on bolts bleeds off relatively quickly under geologic and operational conditions similar to those at the studied mines. The data also showed that within a short time span after installation, the measured loads on active and passive bolts did not differ significantly. This paper compares the results from over 20 bolts of each bolt type that were all 1.8-m (6-ft) -long, 20-mm (0.804-in) nominal diameter Grade 75 rebar and discusses the relevance and shortcomings of the data and bolt performance.